Development of Interactive Learning Media Using Google Sites for Thermochemistry Courses - Pamungkasih, Restika; Erlina, Erlina; Lestari, Ira; Junanto, Tulus; Ulfah, Maria; Mohd Nizam, Dinna Nina (Jurnal Tadris Kimiya, 2024)
Interactive learning media is essential in enhancing student engagement and understanding, particularly in complex subjects like thermochemistry. Google Sites offers a platform to create accessible and interactive educational resources tailored to specific course needs. This study aims to develop, validate, and evaluate student responses to Google Sites-based interactive learning media for a thermochemistry course. The development process followed the analysis, design, development, implementation, and evaluation (ADDIE model). However, this research was limited to the development stage. Validation was conducted on material and media aspects, each reviewed by two validators. Data collection instruments included questionnaires for validation and student responses, involving 32 second-year Chemistry Education students who had previously studied thermochemistry concepts. Validation results yielded scores of 0.94 for the material aspect and 1.00 for the media aspect, indicating excellent validity. Student responses to the media averaged 83%, categorized as very good. The findings suggest that Google Sites-based interactive learning media effectively supports thermochemistry learning, offering a practical and engaging tool for educators and students. Further development and broader implementation of this media could enhance learning outcomes in similar scientific disciplines.